Eficacia de las técnicas de síntesis en la comprensión y recuerdo de textos académicos - Montanero Fernández, Manuel (2001)
In this paper we analyse the advantages that several techniques of study, generally used to synthesise the information (in order to understand and recall expository texts), provide. The data obtained in an empirical study show low usage by pupils of lowest academic level pupils, as well as a greater efficiency in the comprehension of Social scientific texts of those techniques that incorporate more graphic elements (like tables or graphs). Nevertheless, such efficiency seems to depend on the strategic use that the subject makes of the techniques, in function, among other conditions, of the structure of the learning content.